Relevance and importance of effective techniques of teaching vocabulary in different age groups (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
This article explains the reasons why language learning is important and relevant. It also provides information about the most effective methods for language learning. It also provides quotes from several scholars’ research on vocabulary learning. It also discusses the role and relevance of vocabulary learning in establishing diplomatic relations, studying national values, and exchanging ideas.